Social and Religious ideas of Raja Mahender Pratap - rana, Rakesh (Innovative Research Thoughts, 2017)
In the first decades of the twentieth century, Raja Mahendra Pratap Singh was a major political and religious figure in India. When it came to his social beliefs, Raja Mahendra Pratap was an outspoken supporter of the rights and well-being of underrepresented groups. He was a strong advocate for social equality and the empowerment of marginalised groups, especially Dalits and other underprivileged people. He believed that education was the way to empowering these communities, and he tried to spread education among them. Raja Mahendra Pratap had a novel and multifaceted perspective to matters of faith. He adhered to the monotheistic tenets and rejection of idol worship held by the reformist Hindu Arya Samaj, which he supported. But he was also well-known for his advocacy of religious tolerance and his support for the peaceful coexistence of various faiths. He dreamed of a secular India where people of all faiths might coexist peacefully and with mutual respect. Because of his openness to other faiths, he became an icon for religious freedom.